Conceptualization Appropriate Application for Emergency Room Cases for the Unconscious Patients - Mohammed Alduhaiem, Terkee Alshayae, Evan Asfoura, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Applying the new technologies in the health field is growing more and more because of the important effects on the human life. This paper will provide the conceptual model for cloud based application (called Emergency Room (ER) App which support the doctors to improve the diagnostic procedures which will solve an important medical issue at the emergency rooms in case of " an unconscious person". The proposed application will allow storing the sensitive medical information for any person in cloud with high consideration of the privacy aspects. The doctors in the emergency will be able to know all the needed information about the health aspects of the patients directly from the cloud which will be helpful to decide which kind of medicine can be used for recovering the health without any dangerous side effects on those patients. The result will present two concepts the first one will provide the overview about the health records that should be stored in the cloud and the second provide the workflow which explain how the interaction go among of the actors during the application use.